PENGARUH WORK FROM HOMETERHADAP WORK LIFE BALANCE DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING PADA LAKI-LAKI YANG SUDAH MENIKAH DAN MEMILIKI ANAK - Ibnu Hamdan; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to examine the effect of Work From Home on Work-Life Balance with Work Engagement as an Intervening Variable in men who are married and have children. This study uses the Non Probability Sampling method by means of Purposive Sampling. While the sample used is 67 employees. The data analysis technique in this study uses Partial Least Square with SmartPLS software to determine the path coefficient and the effect of the independent variable on the dependent variable. The results showed that Work From Home had a negative and significant effect on Work -Life Balance. Work From Home has a positive and significant effect on Work Engagement. Work Engagement has a positive and significant effect on Work-Life Balance. This study shows that Work Engagement can mediate a significant positive indirect effect between Work From Home on Work-Life Balance.